Pengaruh Senam Hipertensi, Air Rebusan Daun Salam Dan Relaksasi Napas Terhadap Penurunan Tekanan Darah Lansia - Kartika, Iin Ira; Nursobah, Tria; Lilyanti, Henny (Jurnal Kesehatan Bhakti Husada, 2023)
High blood pressure (hypertension) can be treated with pharmacological and non-pharmacological therapies, for example hypertension exercise therapy, giving bay leaf boiled water and deep breathing relaxation for hypertensive elderly at RSLU Karawang. This research is a type of experimental research using a research design in the form of a quasi-experimental non-equivalent control group. The sampling technique in this study was a total sampling of 30 respondents, 15 treatment groups and 15 control groups. Data collection by measuring blood pressure using a sygmanometer and stethoscope with the Wilcoxon statistical test. The mean systolic and diastolic blood pressure in the treatment group before administration of boiled bay leaf water was systolic 150.00 (140-190) mmHg and diastolic 80.00 (90-110) mmHg while after treatment with bay leaf boiled water the average systolic blood pressure was 140.00 Respondents (130-180) mmHg and diastolic 80.00 (70-100) mmHg. The results of the analysis of the Wilcoxon test showed blood pressure after systolic treatment (p=0.001), while diastolic blood pressure (p=0.003). While the results of the Wilcoxon statistical test in the control group before and after being given hypertension exercise therapy, giving deep leaf boiled water and deep breathing relaxation obtained the results of the systolic value before 150.00 and the diastolic value 90.00 (90-110) and the systolic value after 150 (140-170) and a diastolic value of 90.00 (90-110). The results of the analysis of the Wilcoxon test showed that the control group had systolic blood pressure (p=0.366) and 0.564 diastolic blood pressure. It was concluded that there was an effect of giving hypertension exercise therapy, boiled bay leaf water and deep breathing relaxation in hypertensive elderly people at Karawang General Hospital in the treatment group and there was no effect on the control group